Implementasi Metode Background Subtraction dan Morfologi untuk Mendeteksi Objek Bergerak Pada Video - Dede Saptoadi; Fauziah Fauziah; Nur Hayati (Universitas Indraprasta PGRI Jakarta, 2020)
Monitoring systems are a rapidly increasing need in almost all lines of public, such as roads, parks, buildings, terminals and many places that have a monitoring system. Detection adapts learning of moving objects in video observation to obtain results such as the human sense of sight. By detecting objects in the monitoring system, we can determine the frame that shows the position of the moving object. The methods that can be used to de-tect objects are background subtraction and morphology, these methods are considered appro-priate to be implemented in the designed program. The research method used is divided into two stages, namely data collection to collect CCTV video samples and search for related research references. Then the stages that the program goes through include frame extraction, implemen-tation of background subtraction, conversion of grayscale images and converting them into bi-nary form, performing opening morphological operations, making masking and implementing them into video. From the test results the program has a success rate of 93.3% of the test with bright lighting and 83.3% of the test with dim lighting.